Calculation and analysis of the amount of secondary component products of NOX and SO2 on metal oxide surface based on Drifts simulation: A case study of vehicle exhausts emission. Issue 5 (May 2021) - Jia, Lijun; Liang, bo; Li, Cheng; Zhu, Kai; Han, Wenye; Guan, Jie; Gao, Guilan; Li, Yingjie
Abstract: In this paper, the micro reactions of SO2 and NOx in the metal oxides (Fe2 O3, MgO, MnO2, Al2 O3, ZnO, Cuo, SiO2 and Cr2 O3 ) from vehicle exhaust are studied by diffuse reflectance infrared spectroscopy (DRIFTS). The amount of secondary component in PM2.5 is analyzed by observing the synergistic or antagonistic effects of different gases on the surface of different metal oxides. The results show that when SO2 and NO2 coexist, the formation of sulfate is greatly promoted on the surface of Fe2 O3 metal particles, and the intermediate sulfite is formed at the initial stage and then rapidly oxidized to sulfate. Under the condition of oxygen enrichment, the total species content of secondary components of fine particles formed on the surface of metal oxides is Cr2 O3 > Fe2 O3 > MgO > MnO2 > Al2 O3 > ZnO > CuO > SiO2 . because Cr2 O3 has a strong ability to adsorb and activate acid gas, so the content of surface species generated in the micro reaction is more than that of other metal oxides; the metal oxides containing iron, magnesium and manganese can more effectively convert SO2 into sulfate in the presence of NOx, but the sulfate generated on the surface of Cr2 O3, CuO and Al2 O3 decreases, which leads to the difference of metal oxide activity It is caused by the change of metal surface properties. This result has a certain guiding significance for the reaction of SO2 and NOx to metal oxides emitted by motor vehicles in the atmosphere.